Куку Шинель: [роман] / Татьяна Луганцева - Луганцева Татьяна Игоревна (Женщина-цунами, 2008)
Др. произведения авт.: с. 2 Экземпляры: аб. (2010) / Инвентарный номер: 53643 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 83 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44